Impact of serum adipokines on tumor mitotic and apoptotic activity in endometrial cancer - Özdemir, Ayşe; Karlı, Pervin; Kökçü, Arif; Kefeli, Mehmet (Journal of Surgery and Medicine, 2019)
Aim: Endometrial cancer is the most common malignancy of female genital system. Obesity is one of the most important risk factors in endometrial cancer. Adipose tissue functions just like an endocrine organ by secreting many bioactive substances and contributes to tumor development. The aim of this study was to investigate the correlation between serum adipokine levels and tumor mitotic and apoptotic activity levels in endometrial cancer. Methods: We designed a cross-sectional study. After obtaining the approval of Ethics Committee, 38 patients with endometrial cancer admitted between 2014 July-2014 December to Obstetrics and Gynecology outpatient clinic of Ondokuz Mayıs University, Faculty of Medicine were included in the study. Serum leptin and adiponectin levels were measured in 5 cc serum samples taken from the patients preoperatively. The pathology specimens of the patients were semiquantitatively evaluated with immunohistochemical study considering the percentage and intensity of staining for bcl-2 and the percentage of staining for Ki67. Moreover, preoperative estradiol levels, insulin resistance, body fat percentages and body mass index (BMI) values were determined. The Mann Whitney U test, Kruskal Wallis and Spearman’s Correlation test were used statistically. The results were considered statistically significant for P<0.05. Results: The patients included in the study were between 36-82 years of age and the mean age was 62.5 (10.4) years. The mean BMI value of the patients was 31.1 (4.8) kg/m2 (range: 19-38 kg/m2). According to the FIGO 2010 staging system, the distribution of the patients were as follows: 30 patients (78%) Stage 1, 1 patient (2.6%) Stage 2 and 7 patients (18.4%) Stage 3. Of the patients, 6 (15.8%) had grade 1, 20 (52.6%) had grade 2 and 12 (31.6%) had grade 3. Twenty-seven patients were classified as endometrioid type and 11 patients were classified as nonendometrioid type. There was no statistically significant correlation between serum leptin and adiponectin levels and percentage of Ki-67 immunohistochemical staining in tumoral tissue and bcl-2 score (P=0.05). In the immunohistochemical examination of tumoral tissue, it was found that tumor grade statistically significantly increased as the staining percentage for Ki67 increased (r=0.571, P<0.001). There was no statistically significant correlation between Bcl-2 score and tumor grade or stage (P=0.751). It was found that serum leptin levels significantly increased as BMI increased (r=0.341, P=0.036). As HOMA-IR increased, adiponectin level statistically significantly increased (r=0.393, P=0.015). There was also no statistically significant difference between the endometrioid and non-endometrioid groups in terms of leptin, adiponectin and leptin/adiponectin levels (P=0.554, P=0.652). There was no statistically significant difference between the endometrioid and non-endometrioid groups in terms of median BCL-2 score and Ki-67 percentage (P=0.05). Conclusion: There was no correlation between serum leptin and adiponectin levels and Ki-67 immunohistochemical staining percentage and bcl-2 score.